EVALUATION OF EXPERIMENTAL VACCINATION OF WHITE PEKIN DUCKS (ANAS PLATYRHYNCHOS) AGAINST NEWCASTLE DISEASE - Nishizawa, M. [UNESP]; Paulillo, A.c. [UNESP]; Alessi, A.c. [UNESP]; Nunes, A.d. [UNESP]; Campioni, J.m. [UNESP]; Okada, L.s.n. [UNESP]; Doretto, L; Lima, F.s. (Instituto Biológico, 2022)
This study aimed the characterization of the importance of vaccination against Newcastle disease of white Pekin duck (Anas platyrhynchos). There were used 120 Pekin ducks, distributed at random into 4 groups, vaccinated or not. At 60 days of age, all groups were challenged with a pathogenic virus (NDV) suspension, EID50 = 108.15/0.1 mL and a group of Specific Pathogen Free (SPF) chicks were used as control of the virus. Cloacal and tracheal swabs from each bird were collected after 6, 14, 20 and 30 days post-challenge for viral isolation in SPF embryonated eggs. White Pekin ducks of all groups did not demonstrate symptoms of the Newcastle Disease (ND). They were refractory to the ND clinical disease. In Pekin ducks from control group, the viral isolation was obtained from 20 up to 30 days after challenge. The NDV isolation was possible in 100% of SPF chicks that died after challenge with ND clinical signs, suggesting the possible state of carrier of NDV by Pekin ducks. In vaccinated groups, the viral isolation was null. It was also demonstrated therefore the relevance of the vaccination to control the virus dissemination by white Pekin ducks infected with NDV.

O objetivo do trabalho foi estudar a importância da vacinação de marrecos de Pequim (Anas platyrhynchos) contra a Doença de Newcastle (DN). Foram utilizados 120 marrecos, distribuídos aleatoriamente em 4 grupos, vacinados ou não. Aos 60 dias de idade, todos os grupos foram desafiados com uma suspensão de vírus patogênico (VDN), EID50 = 108,15/0,1 mL e um grupo de aves livres de patógenos específicos (SPF) foi utilizado como controle do vírus . Suabes cloacais e traqueais foram colhidos após 6, 14, 20 e 30 dias após o desafio para isolamento viral, realizado em ovos embrionados SPF. Os marrecos de Pequim de nenhum dos grupos demonstraram sinais clínicos da DN, mostrando-se refratários à doença clínica. Nos marrecos do grupo controle, o isolamento viral foi positivo de 20 até 30 dias após o desafio, sugerindo o possível estado de portador do VDN pelos marrecos de Pequim. Foi realizado o isolamento viral em 100% das aves SPF, que apresentaram sinais clínicos e vieram a óbito após o desafio com o VDN. Nos grupos vacinados, o isolamento do VDN foi nulo. Tais dados demonstraram a importância da vacinação para o controle da disseminação do vírus pelos marrecos de Pequim infectados pelo VDN.
ESTUDO DA VACINAÇÃO EXPERIMENTAL DE MARRECOS DE PEQUIM (ANAS PLATYRHYNCHOS) CONTRA A DOENÇA DE NEWCASTLE
Keywords: Pekin duck; Anas platyrhynchos; Newcastle Disease; NDV carrier; vaccination; Marrecos de Pekin; Anas platyrhynchos; Doença de Newcastle; estado de portador; vacinação